Attitude towards mental illness and barriers in seeking psychological help among psychology and nonpsychology students - Getrude Cosmas; Lua, Pei Lin (Penerbit UMS, 2024)
University students’ attitude towards mental health and barriers in seeking help can be affected by numerous factors. Those factors include students’ knowledge of mental health and awareness of obstacles in seeking help. To explore the phenomenon, a study was conducted to examine a comparison between psychology and non-psychology students on their attitude towards mental health and barriers in seeking help. A total of 236 students in one of the local universities in Sabah took part in this study. A study revealed that there was no difference between the two groups of students (psychology vs. non-psychology programs) in terms of their attitudes towards mental illness. However, in terms of care and barriers in seeking psychological help, the study showed that psychology students showed less barriers in seeking psychological help and each of its component (i.e., fear of being stigmatized, trust towards mental health professionals, difficulties in self-disclosure, perceived devaluation and lack of knowledge) in comparison with non-psychology students. Due to these circumstances, it is assumed that knowledge and awareness on mental illness may reduce barriers in seeking psychological help and increase participants’ knowledge on care and treatment of mental illness. Therefore, mental health programs/campaigns should be implemented continuously as an effective way to tackle participants’ barriers in seeking psychological help.